Point Counter-Point Learning Strategy on the Subject of Social Sciences to Improve the Learning Achievement - Nurhalimah, Nurhalimah; Ponidi, Ponidi (Graduate Program Magister Manajemen Pendidikan, 2025)
This research aims to see how the Point Counter-Point learning strategy in social studies subjects can improve student learning achievement at Al-Hidayah Medan Private Junior High School (SMP). By focusing on social studies learning, where the points in the curriculum are key in understanding various social, economic and political aspects, this learning strategy becomes very relevant. This research uses a qualitative methodology using descriptive methods. This approach aims to provide a systematic, accurate and factual description of the phenomenon being studied. The results of this research show that the Point Counter-Point learning strategy makes a significant contribution to increasing student learning achievement. This is reflected in increased student involvement in discussions, development of critical thinking skills, as well as improvements in the way students organize and convey their ideas. This research provides in-depth insight into how this strategy functions in the learning context in class VII, as well as how it can improve students’ understanding and learning achievement in social studies subjects.